2021
DOI: 10.1016/j.csbj.2021.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Formation, characterization and modeling of emergent synthetic microbial communities

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 95 publications
1
19
0
Order By: Relevance
“…A recent study has shown Pseudomonas sp. GM17 to have negative interactions with majority of the microbial members in this 10-member DefCom [ 24 ]. In fact, notable changes in relative protein abundances were identified for a sensor histidine kinase GacS (WP_007927747.1), which plays a role in sensing environmental signals and GacA (WP_020295157.1), a response regulator activated by GacS (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study has shown Pseudomonas sp. GM17 to have negative interactions with majority of the microbial members in this 10-member DefCom [ 24 ]. In fact, notable changes in relative protein abundances were identified for a sensor histidine kinase GacS (WP_007927747.1), which plays a role in sensing environmental signals and GacA (WP_020295157.1), a response regulator activated by GacS (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…AP49, Paraburkholderia sp. BT03 also has a similar growth rate [ 24 ]. However, these microbes did not represent a significant portion of the stable community.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthetic microbial communities have been developed for both rhizosphere and phyllosphere communities in several species: most notably Arabidopsis , as well as maize, sorghum, and duckweed, among others, with varying levels of phylogenetic representation ( Table 1 ). Varied approaches have been taken for designing synthetic communities with the ultimate goal of developing a community representative of the function and interactions of a natural, complex microbiome (e.g., Timm et al, 2016 ; Wang et al, 2021 ). Co-occurrence network analyses are commonly used to identify core functional microbiomes – a reduced subset of microbial species that captures the main metabolic processes performed by a community ( Toju et al, 2020 ), but other methods recognize the inherent complexity of non-equilibrium microbe-environment interactions and incorporate time-series data with empirical methods ( Deyle et al, 2016 ; Suzuki et al, 2017 ).…”
Section: Overview Of Synthetic Communities In Plant Systemsmentioning
confidence: 99%